Políticas outras - Chieffi, Paula (2009)
Based on concepts and thought of Gilles Deleuze and Félix Guattari, the present research aims at outlining contemporary politics action. In this direction were interviewed six different people - different experiences, different social practices. This dissertation dialogues with art and political anthropology to compose desiring forces able to enlarge the potency to say yes to other forms of existence. The intensive experience and its expression, multiplicity and the direct act characterize politics as nomadic, disruptive and intense